Enhanced Methanol Electro‐Oxidation Activity of Nanoclustered Gold. Issue 27 (7th February 2021) - Yadav, Anupam; Li, Yejun; Liao, Ting‐Wei; Hu, Kuo‐Juei; Scheerder, Jeroen E.; Safonova, Olga V.; Höltzl, Tibor; Janssens, Ewald; Grandjean, Didier; Lievens, Peter
Abstract: Size‐selected 3 nm gas‐phase Au clusters dispersed by cluster beam deposition (CBD) on a conducting fluorine‐doped tin oxide template show strong enhancement in mass activity for the methanol electro‐oxidation (MEO) reaction compared to previously reported nanostructured gold electrodes. Density functional theory‐based modeling on the corresponding Au clusters guided by experiments attributes this high MEO activity to the high density of exposed under‐coordinated Au atoms at their faceted surface. In the description of the activity trends, vertices and edges are the most active sites due to their favorable CO and OH adsorption energies. The faceted structures occurring in this size range, partly preserved upon deposition, may also prevent destructive restructuring during the oxidation‐reduction cycle. These results highlight the benefits of using CBD in fine‐tuning material properties on the nanoscale and designing high‐performance fuel cell electrodes with less material usage. Abstract : Size‐selected Au clusters dispersed by cluster beam deposition on fluorine‐doped tin oxide show strong enhancement of methanol electro‐oxidation activity. A detailed characterisation of their structure in combination with density functional theory‐based modelling attribute this enhancement to the high density of exposed under‐coordinated Au atoms at their faceted surface. Vertices and edges are the most active sites due to their favorable CO and OH adsorption energies.